2008
DOI: 10.1007/s10840-008-9286-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative atrial fibrillation management by selective epicardial vagal fat pad stimulation

Abstract: Epicardial RIFPS represents an effective and feasible technique to decrease VR during POAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…21 Stimulation of epicardial and endocardial electrodes placed in the AV nodal FP region can cause complete AV block, or markedly slow the ventricular rate response during atrial fibrillation. 13,14,21,22 Therefore, we do not anticipate too discrepant observations once tested in children undergoing OHS.…”
Section: Study Limitationsmentioning
confidence: 86%
See 1 more Smart Citation
“…21 Stimulation of epicardial and endocardial electrodes placed in the AV nodal FP region can cause complete AV block, or markedly slow the ventricular rate response during atrial fibrillation. 13,14,21,22 Therefore, we do not anticipate too discrepant observations once tested in children undergoing OHS.…”
Section: Study Limitationsmentioning
confidence: 86%
“…In a similar animal model of sustained atrial fibrillation, Schauerte et al 12 demonstrated using an endocardial approach to AV nodal FP stimulation that the parasympathetic effects were sustained for at least a period of 20 hours and were related to the intensity of nerve stimulation. Rossi et al 13 The use of this technique for control of postoperative atrial fibrillation and atrial tachycardias and its applicability to a younger age group is a logical extension of the studies reported to date. However, no previous data existed on the effects of right inferior FP stimulation on postoperative JET.…”
Section: Pauza Et Almentioning
confidence: 99%
“…These nerve fibers extend through the interatrial septum at the coronary sinus ostium or the posteroseptal right atrium. [9][10][11][12][13][14] After right ventricular lead implantation, a standard atrial screw in lead (Medtronic type 5076 [2] and 4076 [29] or St Jude's 2088TC [1]) was directed and screwed into the posteroseptal region of the coronary sinus ostium. The septum is recognized as a feasible and safe site for chronic pacing to reduce paroxysmal AF recurrences, AF burden, and progression to permanent AF, with the rationale of reducing the duration of atrial activation.…”
Section: Atrial Lead Implant Proceduresmentioning
confidence: 99%
“…In the United States, the cost for intensive care for postoperative AF is substantial, with estimated annual expenditures exceeding 1 billion dollars [13,14]. Prediction of incoming AF after CABG soon enough to allow for prophylactic intervention would thus be helpful and cost-effective [2,3,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental mechanisms responsible for AF, especially for post-surgery patients, is still not well understood [2,3,12]. Electrical properties, such as heterogeneous spatial distribution of excitability and repolarization, may play an important role in the generation and perpetuation of the arrhythmia [15][16][17].…”
Section: Introductionmentioning
confidence: 99%